The mechanism of chromate reduction by Thermus scotoductus SA-01 - Opperman, Diederik Johannes (University of the Free State, 2008)
English: Recent contamination of the environment with Cr(VI) through various industrial activities is becoming an increasing problem to which microbial Cr(VI) reduction could prove an important alternative solution compared to currently available chemical and physical treatment options. Cr(VI) is highly toxic and has been shown to be a mutagen and carcinogen, whereas Cr(III) is considered relatively innocuous. A variety of Cr(VI)-resistant and reducing bacteria have been isolated from diverse environments both contaminated and uncontaminated with Cr(VI). In 1999, Kieft and co-workers isolated a Thermus scotoductus strain from groundwater of a South African gold mine at a depth of 3.2 km. This thermophilic bacteria was shown to be able to readily reduce a variety of metals including Fe(III), Mn(IV), Co(III)-EDTA, U(VI) and Cr(VI). This ubiquitous nature of Cr(VI) reducing bacteria and the fact that Cr(VI) rarely occurs naturally in the environment, has led several researches to proposed that these chromate reducing properties is the serendipitous activity of enzymes with other primary physiological functions. Thermus scotoductus SA-01 has the ability to tolerate up to 0.5 mM Cr(VI) during growth in a complex organic medium and reduce Cr(VI) under growth and non-growth conditions. The rate of chromate reduction is dependent on pH, temperature, initial Cr(VI) concentration and is abolished by metabolic inhibiters. Chromate reduction was catalyzed by cellular extracts using NADH as an electron donor indicating the chromate reduction mechanisms to be enzymatic. Subcellular fractionation studies indicated that Thermus scotoductus SA-01 possesses more than one chromate reduction mechanisms. A novel cytoplasmic chromate reductase was purified to homogeneity and shown to couple the oxidation of NAD(P)H to the reduction of Cr(VI). This homodimeric protein consisted of monomers of approximately 36 kDa with a non-covalently bound FMN and required the divalent metal Ca2+ for activity. The enzyme was optimally active at 65°C and a pH of 6.3, reducing 2 mol of NAD(P)H per mol Cr(VI), suggesting a mixed one- and two-electron transfer mechanism. N-terminal sequencing and screening of a genomic library of T. scotoductus SA-01 using a DIG-labelled DNA probe, revealed the cytoplasmic chromate reductase to be encoded for by an ORF of 1050 bp under the regulation of an E. coli σ70-like promoter. Sequence analysis showed the chromate reductase to be related to the Old Yellow Enzyme (OYE) family and in particular some xenobiotic reductases. The membrane-associated chromate reductase was also purified to homogeneity and shown to be distinct from the above mentioned cytoplasmic chromate reductase. The membrane-assocated reductase appears to be peripherally-associated with the membrane of T. scotoductus and consists of two identical subunits of approximately 48 kDa. The chromate reductase contained a non-covalently bound FAD co-factor and was optimally active at 65°C and a pH of 6.5. Through N-terminal sequencing and screening of a genomic library, the membrane-associated chromate reductase was identified as homologous to the dihydrolipoamide dehydrogenase gene, encoded for by a 1386 bp ORF and located within a probable pyruvate dehydrogenase operon. Although neither of these enzymes are dedicated physiological chromate reductases, their catalytic efficiency toward Cr(VI) as substrate proved to be superior than that found for other chromate reductases described in literature, which include the nitroreductases and quinone reductases isolated from Pseudomonas putida and Escherichia coli Both the cytoplasmic and membrane-associated chromate reductases were heterologously overproduced in E. coli and T. thermophilus as active, soluble enzymes. Kinetic studies of the recombinant proteins showed that the recombinant chromate reductases expressed in T. thermophilus were more catalytic efficient than their E. coli-expressed counterparts. Although structurally no differences could be observed using UV-vis and circular dichroism spectroscopy, the T. thermophilus-expressed recombinant cytoplasmic chromate reductase proved to be more stable under extreme chemical and thermal conditions.

Afrikaans: Kontaminasie van die omgewing met Cr(VI) deur verskeie industriële aktiwiteite word ŉ toenemende probleem waarvan mikrobiese Cr(VI) reduksie ŉ belangrike alternatief tot die huidige beskikbare chemiese en fisiese behandeling opsies is. Cr(VI) is hoogs toksies en is bewys om mutagenies en karsinogenies te wees, teenoor Cr(III) wat beskou word as relatief onskadelik. ŉ Verskeidenheid Cr(VI)-tolerante en reduserende bakterieë is geïsoleer vanaf diverse omgewings wat beide gekontamineer en ongekontamineer is met Cr(VI). In 1999, het Kieft en medewerkers ŉ Thermus scotoductus spesie geïsoleer vanuit grondwater afkomstig vanaf ŉ Suid Afrikaanse goud myn, 3.2 km onder die grond. Daar is bewys dat hierdie termofiliese bakterieë ŉ verskeidenheid metale insluitende Fe(III), Mn(IV), Co(III)-EDTA, U(VI) en Cr(VI) kan reduseer. Die algemene voorkoms van Cr(VI) reduserende bakterieë en die feit dat Cr(VI) nie natuurlik in die omgewing voorkom nie, het daartoe gelei dat verskeie navorsers voorgestel het dat hierdie Cr(VI) reduserende eienskap ŉ nie spesifieke reaksie is deur ensieme met ander primêre fisiologiese funksies. Thermus scotoductus SA-01 het die vermoë om 0.5 mM Cr(VI) te weerstaan tydens groei in ŉ komplekse organiese medium en reduseer Cr(VI) tydens groei en nie-groei kondisies. Die tempo van chromaat reduksie is afhanklik van pH, temperatuur asook aanvanklike Cr(VI) konsentrasie en word geïnhibeer deur metaboliese inhibitors. Chromaat reduksie word gekataliseer deur sellulêre ekstrakte en maak gebruik van NADH as elektron donor wat wys dat die chromaat reduksie ensimaties is. Subsellulêre fraksionering wys dat Thermus scotoductus SA-01 het meer as een chromaat reduserende meganismes. ŉ Eiesoortige sitoplasmiese chromaat reduktase was gesuiwer en daar is gewys dat die oksidasie van NAD(P)H verbind kan word met die reduksie van Cr(VI). Hierdie dimeriese proteïen bestaan uit twee identiese monomere van ongeveer 36 kDa met ŉ nie-kovalente gebinde FMN en benodig die divalente metaal Ca2+ vir aktiwiteit. Die ensiem was optimaal aktief by 65°C met ŉ pH van 6.3. Twee mol NAD(P)H word gereduseer per mol Cr(VI) wat ŉ gemengde een- en twee-elektron oordrag meganisme voorstel. N-terminale aminosuuropeenvolging bepaling en evaluering van ŉ genomiese biblioteek van T. scotoductus SA-01, deur gebruik te maak van ‘n DIG-gemerkte DNS priemstuk, het gewys dat die sitoplasmiese chromaat reduktase gekodeer word deur ŉ leesraam van 1050 bp wat onder die regulering van ŉ E. coli σ70-tiepe promotor is. Basispaaropeenvolging analise wys dat die chromaat reduktase verwant is aan die Ou Geel Ensiem (OGE) familie, meer spesifiek die xenobiotiese reduktases. Die membraan-geassosieerde chromaat reduktase is ook gesuiwer as ŉ homogeniese preparaat en dit is bewys om anders as die bogenoemde sitoplasmiese chromaat reduktase te wees. Die membraan-geassosieerde reduktase blyk periferaal-geassosieerd te wees en bestaan uit twee identiese subeenhede van ongeveer 48 kDa. Die chromaat reduktase bevat ‘n nie-kovalent gebinde FAD kofaktor en was optimaal aktief by 65°C by ‘n pH van 6.5. Deur N-terminaal aminosuuropeenvolging bepaling en evaluering van ŉ genomiese biblioteek is die membraan-geassosieerde chromaat reduktase geen geïdentifiseer as ŉ homoloog van die dihidrolipoamied dehidrogenase geen, wat gekodeer word deur ŉ leesraam van 1386 bp en vorm deel van ŉ moontlike piruvaat dehidrogenase operon. Alhoewel nie een van die ensieme ŉ egte fisiologiese chromaat reduktase is nie, is bewys dat beide se katalitiese effektiwiteit tot Cr(VI) as substraat beter is as ander chromaat reductases beskryf in literatuur, wat insluit die nitroreduktases en die quinien reduktase vanaf Pseudomonas putida en Escherichia coli. Beide die sitoplasmiese en membraan-geassosieerde chromaat reduktases was uitgedruk in E. coli en T. thermophilus as aktiewe, oplosbare ensieme. Kinetiese studies van die rekombinante proteïene wys dat die chromaat reduktases uitgedruk in T. thermophilus meer katalities effektief was as proteïene uitgedruk in E. coli. Alhoewel daar geen strukturele verskille waargeneem is met UV-vis en sirkulêre dichroisme spektrofotografie nie, was die T. thermophilus uitgedrukte sitoplasmiese chromaat reduktase meer stabiel onder ekstreme chemiese en termiese toestande.
Keywords: Metals -- Biodegradation; Thermophilic bacteria; Chromium -- Environmental aspects; Bioremediation; Thesis (Ph.D. (Microbial, Biochemical and Food Biotechnology))--University of the Free State, 2008